Vitamin B1 and B12 Uptake and Cycling by Plankton Communities in Coastal Ecosystems - Koch, Florian; Hattenrath-Lehmann, Theresa K.; Goleski, Jennifer A.; Sanudo-Wilhelmy, Sergio; Fisher, Nicholas S.; Gobler, Christopher J. (Frontiers in Microbiology, 2012)
While vitamin B12 has recently been shown to co-limit the growth of coastal phytoplankton assemblages, the cycling of B-vitamins in coastal ecosystems is poorly understood as planktonic uptake rates of vitamins B1 and B12 have never been quantified in tandem in any aquatic ecosystem. The goal of this study was to establish the relationships between plankton community composition, carbon fixation, and B-vitamin assimilation in two contrasting estuarine systems. We show that, although B-vitamin concentrations were low (pM), vitamin concentrations and uptake rates were higher within a more eutrophic estuary and that vitamin B12 uptake rates were significantly correlated with rates of primary production. Eutrophic sites hosted larger bacterial and picoplankton abundances with larger carbon normalized vitamin uptake rates. Although the >2 µm phytoplankton biomass was often dominated by groups with a high incidence of vitamin auxotrophy (dinoflagellates and diatoms), picoplankton (< 2 µm) were always responsible for the majority of B12-vitamin uptake. Multiple lines of evidence suggest that heterotrophic bacteria were the primary users of vitamins among the picoplankton during this study. Nutrient/vitamin amendment experiments demonstrated that, in the Summer and Fall, vitamin B12 occasionally limited or co-limited the accumulation of phytoplankton biomass together with nitrogen. Combined with prior studies, these findings suggest that picoplankton are the primary producers and users of B-vitamins in coastal ecosystems and that rapid uptake of B-vitamins by heterotrophic bacteria may sometimes deprive larger phytoplankton of these micronutrients and thus influence phytoplankton species succession.